Analysis of Financial Market in Malaysia Using ARCH and GARCH-Type Model - Chu, Wei Hao; Saharan, Sabariah (Enhanced Knowledge in Sciences and Technology, 2024)
The stock market is a platform for investors to buy and sell shares of ownership in companies. The foreign exchange market is a global decentralized marketplace for individuals and businesses to trade currencies for international investment. In this study, ARCH and GARCH models was apply to analyze the volatility from both the banking stock such as CIMB, Maybank and Public Bank and Forex markets, MYR/USD. Parameters such as Log Likelihood (LL), Akaike Info Criterion (AIC), Schwarz Criterion (SC) and Hannan-Quinn Criterion (HQC) will used to compared the ARCH and GARCH model. Moreover, adjusted R-Squared (ARS), standard error regression (SER) and sum squared residual (SSR) will be used to decide the most volatile market within the ARCH and GARCH model. Next, calculating simple return rates is to identify the return rates for stock and Forex market. Based on the result, Forex market (MYR/USD) is much more volatile than the stock market (CIMB, Maybank and Public Bank). This indicate that the prices of currencies can fluctuate more rapidly than the prices of the stocks. However, stock market has higher return than the forex market. This means that investors can expect to make more money over the long term by investing in stocks than by investing in currencies. The personal choice of investing in either stock or Forex market depends on the individual risk tolerance.